Neural correlates of mirror visual feedback-induced performance improvements: a resting-state fMRI study - Rjosk, Viola; Lepsien, Joeran; Kaminski, Elisabeth; Hoff, Maike; Sehm, Bernhard; Steele, Christopher J.; Villringer, Arno; Ragert, Patrick (Frontiers in Human Neuroscience, 2017)
Mirror visual feedback (MVF) is a promising approach to enhance motor performance without training in healthy adults as well as in patients with focal brain lesions. There is preliminary evidence that a functional modulation within and between primary motor cortices as assessed with transcranial magnetic stimulation might be one candidate mechanism mediating the observed behavioral effects. Recently, studies using task-based functional magnetic resonance imaging (fMRI) have indicated that MVF-induced functional changes might not be restricted to the primary motor cortex but also include higher order regions responsible for perceptual-motor coordination and visual attention. However, aside from these instantaneous task-induced brain changes, little is know about learning-related neuroplasticity induced by MVF. Thus, in the present study, we assessed MVF-induced functional network plasticity with resting-state fMRI (rs-fMRI). We performed rs-fMRI of 35 right-handed, healthy adults before and after performing a complex ball-rotation task. The primary outcome measure was the performance improvement of the untrained left hand before and after right hand training with MVF (mirror group, n=17) or without MVF (control group, n=18). Behaviorally, the mirror group showed superior performance improvements of the untrained left hand. In resting-state functional connectivity, an interaction analysis between groups showed changes in left visual cortex (V1, V2) revealing an increase of centrality in the mirror group. Within group comparisons showed further functional alterations in bilateral primary sensorimotor cortex, left visual cortex (V4) and left anterior intraparietal sulcus in the mirror group, only. Importantly, a correlation analysis revealed a linear positive relationship between MVF-induced improvements of the untrained left hand and functional alterations in left primary sensorimotor cortex. Our results suggest that MVF-induced performance improvements are associated with functional learning-related brain plasticity and have identified additional target regions for non-invasive brain stimulation techniques, a finding of potential interest for neurorehabilitation.